Biomedical Analytics of Four Chinese Medicinals in Treatment of Insomnia Based on Network Pharmacology. (31st May 2022) - Deng, Qiyue; Huang, Libing; Yu, Fanjun; Lin, Jiahui; Hu, Lijuan; Zhao, Jing; Pan, Litao; Kui, Yu; Wu, Shiheng
Abstract : Aim. Our aim is to recommend the appropriate Chinese medicinals in clinical treatment of insomnia, which are suānzăorén (Semen Ziziphi Spinosae), chuānxiōng (Rhizoma Chuanxiong), fúlíng (Poria), and báisháo (Radix Paeoniae Alba). Method. Based on network pharmacology, the active molecules and mechanism of these four Chinese medicinals treating insomnia were sought and analyzed. The components of the four Chinese medicinals with potential activity were collected and screened. Moreover, the recollected human disease-related targets were correlated through Cytoscape 3.8.2, and the network diagram of drug component disease targets was drawn. Based on the human protein-protein interaction database, the above network diagram was imported to establish the protein-protein interaction (PPI) and composite target pathway (C-T-P) networks. After selecting important information, the pathway analysis was carried out to show the biological process, core target, and core pathway of insomnia treatment. Result. In this study, 44 active components and 81 drug-disease common targets were obtained; 307 key targets were found in the PPI network; a core cluster composed of 14 nodes and 50 functional associations was found. Conclusion. In summary, the four Chinese medicinals' effective components and main mechanism of in the treatment of insomnia may be related to their participation in the regulation of endocrine. Compared with the existing network pharmacological analysis results of SuānZăoRénTāng (Sour Jujube Decoction), which is commonly used in insomnia, they have similar effects on the immune system and HPA axis, while the focus of the four Chinese medicinals is mainly on endocrine regulation, and SuānZăoRénTāng (Sour Jujube Decoction) is mainly on anti-inflammatory effect.